Negotiating Latinidad : intralatina/o lives in Chicago - Aparicio, Frances R. (Latinos in Chicago and the Midwest., 2019)
"Negotiating Latinidad shares the family experiences of twenty Intralatino/as who were born in, and/or grew up in Chicago and have negotiated the national communities embodied in their nuclear and extended families. Intralatino/as are Latino/as of mixed nationalities, such as MexiRicans, MexiGuatemalans, CubanRicans, and SalvadoRicans. These children of Latino/a parents of different Latino American nationalities are the biological instantiation of Latinidad. Their personal lives and their everyday experiences negotiating various national communities, most evidently in their families, have not yet been documented, analyzed, or integrated into our knowledge about U.S. Latino/as. In the first study of this group, Frances R. Aparicio discovered that Intralatino/as see themselves as true Latino/as, with mixed identities, who are able to understand difference and boundaries more easily than others. Yet they also have, in their own family situations, conflicts, tragedies, and celebrations, experienced the pain of (non)belonging, whether in a brief moment of social interaction with others or in the lengthier unfolding of their family dramas, conflicts, and challenges. This book contributes to efforts to reaffirm the critical role of social identities for postcolonial, subordinated minorities in a globalizing world that increasingly renders identity politics and social identities unimportant. The book is also about the Intralatino/a subjectivities that inevitably prompts the question of whether U.S. Latino/as will eventually become a melting pot of nationalities"--